Antibacterial Activity Of Prodigiosin Extract Against Opportunistic Shrimp Gut Bacteria Isolated From Litopenaeus Vannamei - Mohamad Suhaimi, Nurul Syakirah (2022)
Disease in cultivated shrimp nowadays has seen as the critical problem to the aquaculture world production. The excessive and abusive used of antibiotic to treat bacterial infection, however, have driven the development of antimicrobial resistant. These issues have raised many problems to the shrimp aquaculture industry and nearby environment. Therefore, searching of new treatment method is important especially from natural substances against opportunistic and pathogenic bacteria. The objective of this research study was to assess the antibacterial activity of prodigiosin extract of marine bacterium Serratia marcescens IBRL USM84 against opportunistic bacteria isolated from the infected shrimp gut of L. vannamei. Extracellular crude extract was selected as it showed a better inhibitory effect with faster killing rate on tested bacteria compared to intracellular crude extract.